Positive electrode material and preparation method thereof, positive electrode plate and lithium battery
By covering the surface of the lithium phosphate positive electrode material with carbon materials containing hydrocarbon groups, halogen atoms, and nitro groups, the problem of water absorption of the material is solved, and the cycle life and conductivity of the battery are improved.
Patent Information
- Application Number
- CN202411722600.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium phosphate positive electrode material is easy to absorb water, making it difficult to control the moisture in the battery, affecting the stability of the material and the cycle life of the battery.
A layer of carbon material is coated as a protective shell on the surface of the lithium phosphate positive electrode material. The carbon coating layer contains one or more groups of hydrocarbon groups, halogen atoms, and nitro groups, and is hydrophobic.
The carbon cladding layer reduces the contact between the lithium phosphate positive electrode material and the external water, improves its water absorption, improves the cycle life of the battery cell, and improves the conductivity of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium battery. Background Art
[0002] Lithium battery positive electrode materials are mainly lithium phosphate positive electrode materials and ternary materials, among which lithium manganese iron phosphate is regarded as an important upgrade direction for lithium iron phosphate batteries and has broad application prospects. Since lithium phosphate positive electrode materials have the disadvantage of poor conductivity, they need to be nano-sized in order to improve their conductivity. However, the nano-sized lithium phosphate positive electrode materials have small particle size and large specific surface area, which makes them easy to absorb water, making it difficult to control the moisture content of the battery, affecting the stability of the lithium phosphate positive electrode materials, and further affecting the battery cycle life. Summary of the invention
[0003] The embodiments of the present invention provide a positive electrode material and a preparation method thereof, a positive electrode plate and a lithium battery, which can improve the technical problem of easy water absorption of lithium phosphate positive electrode materials.
[0004] In a first aspect, an embodiment of the present invention provides a positive electrode material, including a core and a carbon coating layer, wherein the carbon coating layer is at least partially coated on the surface of the core, the material of the core includes a lithium phosphate positive electrode material, and the carbon coating layer contains a hydrocarbon group 、 One or more groups of halogen atoms and nitro groups.
[0005] In one embodiment, the lithium phosphate positive electrode material includes at least one of lithium iron phosphate and lithium manganese iron phosphate; and / or
[0006] The carbon coating layer is formed by carbonizing a carbon source, wherein the carbon source contains a hydrocarbon group 、 One or more groups of halogen atoms and nitro groups.
[0007] In one embodiment, the positive electrode material satisfies: 14.5≤SSA / D50≤28.5, wherein SSA is the specific surface area of the positive electrode material, in m 2 / g, D50 is the particle size of the positive electrode material, in μm.
[0008] In one embodiment, the SSA is 15m 2 / g-25m 2 / g; and / or
[0009] The D50 is 0.5 μm-1.5 μm.
[0010] In one embodiment, the thickness of the carbon coating layer is 0.1 μm-0.2 μm; and / or
[0011] The mass content of the carbon coating layer in the positive electrode material is 1.5%-2.0%.
[0012] In a second aspect, an embodiment of the present invention provides a method for preparing a positive electrode material, comprising the following steps:
[0013] Providing a core material and a carbon source, and coating the carbon source on the surface of the core material to obtain a positive electrode material precursor, wherein the core material includes a lithium phosphate positive electrode material, and the carbon source includes one or more groups selected from hydrocarbon groups, halogen atoms, and nitro groups;
[0014] The positive electrode material precursor is subjected to a first solid phase sintering to obtain a positive electrode material.
[0015] In one embodiment, coating the carbon source on the surface of the core material comprises:
[0016] The carbon source is dispersed in an organic solvent to obtain a dispersion, and the dispersion is then coated on the surface of the core material by spray drying.
[0017] In one embodiment, the carbon source contains a hydrocarbon group 、 One or more of halogen atoms, nitro groups; and / or
[0018] The mass concentration of the carbon source in the dispersion is 10%-20%; and / or
[0019] The drying temperature of the spray drying is 60°C-80°C.
[0020] In one embodiment, the method for preparing the lithium phosphate positive electrode material comprises the following steps:
[0021] Providing a manganese source, an iron source, a phosphorus source and a lithium source or providing an iron source, a phosphorus source and a lithium source, mixing them, and grinding them with water to obtain a mixed solution;
[0022] The mixed solution is subjected to a second solid phase sintering to obtain a lithium phosphate positive electrode material.
[0023] In one embodiment, the grinding time is 2h-6h; and / or
[0024] The temperature of the second solid-phase sintering is 300° C.-1200° C., and the time of the second solid-phase sintering is 6 h-12 h.
[0025] In one embodiment, the first solid phase sintering is performed under an inert gas atmosphere; and / or
[0026] The temperature of the first solid-phase sintering is 300° C.-1200° C., and the time of the first solid-phase sintering is 6 h-12 h.
[0027] In a third aspect, an embodiment of the present invention provides a positive electrode plate, comprising a current collector and an active material layer disposed on the current collector, wherein the active material layer comprises the above-mentioned positive electrode material, and the contact angle θ of the surface of the active material layer to water is ≥55°.
[0028] In a fourth aspect, an embodiment of the present invention provides a lithium battery, comprising the above-mentioned positive electrode plate.
[0029] Beneficial effects of the embodiments of the present invention:
[0030] In an embodiment of the present invention, a layer of carbon material is coated on the surface of the lithium phosphate positive electrode material as a protective shell, and the carbon coating layer is hydrophobic and contains one or more groups of hydrocarbon groups, halogen atoms, and nitro groups, so that the prepared positive electrode material has hydrophobic properties, thereby reducing the contact between the lithium phosphate positive electrode material and external water, improving its strong water absorption problem, and thereby increasing the cycle life of the battery cell. DETAILED DESCRIPTION
[0031] The technical solution of this application is as follows:
[0032] In a first aspect, an embodiment of the present application provides a positive electrode material, including a core and a carbon coating layer, wherein the carbon coating layer is at least partially coated on the surface of the core body, the material of the core body includes a lithium phosphate positive electrode material, and the carbon coating layer contains one or more groups selected from hydrocarbon groups, halogen atoms, and nitro groups.
[0033] In the present application, a layer of carbon material is coated on the surface of the lithium phosphate positive electrode material as a protective shell. The carbon coating layer is hydrophobic and contains one or more groups of hydrocarbon groups, halogen atoms, and nitro groups. This makes the prepared positive electrode material have hydrophobic properties, thereby reducing the contact between the lithium phosphate positive electrode material and external water, improving its strong water absorption problem, and then increasing the cycle life of the battery cell; at the same time, the carbon coating layer can improve the conductivity of the lithium phosphate positive electrode material and improve the problem of poor conductivity of the lithium phosphate positive electrode material itself.
[0034] In some embodiments, the lithium phosphate positive electrode material includes at least one of lithium iron phosphate and lithium manganese iron phosphate.
[0035] In the present application, water absorption of the nano-sized lithium iron manganese phosphate material will intensify the Jahn-Teller effect of Mn. Carbon coating of the lithium iron manganese phosphate can effectively reduce its absorption of water, thereby improving the stability of the lithium iron manganese phosphate material.
[0036] In some embodiments, the positive electrode material satisfies: 14.5≤SSA / D50≤28.5, for example, SSA / D50 can be 14.5, 15.5, 16.5, 17.5, 18.5, 19.5, 20.5, 21.5, 22.5, 23.5, 24.5, 25.5, 26.5, 27.5, 28.5, etc., wherein SSA is the specific surface area of the positive electrode material, in m 2 / g, D50 is the particle size of the positive electrode material, in μm. In this way, the positive electrode material can have good hydrophobicity.
[0037] In some embodiments, SSA is 15m 2 / g-25m 2 / g, for example, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g, 25m 2 / g, etc. In this way, the positive electrode material can have good performance and is not easy to absorb water. If the specific surface area is too large, the positive electrode material is easy to absorb water, and if the specific surface area is too small, the performance of the positive electrode material will be affected.
[0038] In some embodiments, D50 is 0.5 μm-1.5 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, etc. In this way, the positive electrode material can have good rate performance and good processing performance. If D50 is too large, the rate performance of the positive electrode material will be affected, and if D50 is too small, the processing performance of the positive electrode material will deteriorate.
[0039] In some embodiments, the carbon coating layer is formed by carbonizing a carbon source, wherein the carbon source contains a hydrocarbon group. 、 One or more groups of halogen atoms and nitro groups. In this way, the coating layer can have hydrophobic groups, so that the surface of the positive electrode material has hydrophobic groups and plays a protective role on the core body.
[0040] In the present application, the carbon source can be a surface-modified (nitrated and / or halogenated) carbonaceous material, including nitrated and / or halogenated carbon nanotubes, nitrated and / or halogenated graphene, nitrated and / or halogenated carbon nanofibers, nitrated and / or halogenated polydimethylsiloxanes, nitrated and / or halogenated polycarbonates, nitrated and / or halogenated polyolefins, and nitrated and / or halogenated polyacrylonitrile. The carbon source can also include polydimethylsiloxane, polycarbonate, polyolefin, and polyacrylonitrile.
[0041] Nitration is the introduction of nitro (-NO2) functional groups on the surface of carbon-containing materials (such as carbon nanotubes, graphene, carbon nanofibers, polydimethylsiloxane, polycarbonate, polyolefins, polyacrylonitrile), and the carbon-containing material can be nitrated by using a mixed acid of concentrated nitric acid and concentrated sulfuric acid. Halogenation is the introduction of halogen atoms on the surface of carbon-containing materials, which can be achieved by directly reacting the carbon material with the halogen or reacting with the halogen in the presence of a catalyst. In some embodiments, the thickness of the carbon coating layer is 0.1 μm-0.2 μm, for example, it can be 0.10 μm, 0.11 μm, 0.12 μm, 0.13 μm, 0.14 μm, 0.15 μm, 0.16 μm, 0.17 μm, 0.18 μm, 0.19 μm, 0.20 μm, etc. In this way, the core can be fully protected, while the positive electrode material has good performance. If the carbon coating is too thick, it will affect the performance of the positive electrode material, and if it is too thin, it will not provide adequate protection for the core.
[0042] In some embodiments, the mass content of the carbon coating layer in the positive electrode material is 1.5%-2.0%, for example, it can be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, etc.
[0043] In a second aspect, the present invention also provides a method for preparing a positive electrode material, comprising the following steps:
[0044] S1. Provide a core material and a carbon source, and coat the carbon source on the surface of the core material to obtain a positive electrode material precursor, wherein the core material includes a lithium phosphate positive electrode material, and the carbon source includes a hydrocarbon group 、 One or more groups of halogen atoms and nitro groups;
[0045] S2. Performing a first solid-phase sintering on the cathode material precursor to obtain the cathode material.
[0046] In some embodiments, the first solid phase sintering is performed under an inert gas atmosphere.
[0047] In some embodiments, the temperature of the first solid phase sintering is 300°C-1200°C, for example, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc., and the time of the first solid phase sintering is 6h-12h, for example, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc. In this way, the carbon source and the core body can be fully combined, thereby improving the performance of the positive electrode material.
[0048] In some embodiments, coating the carbon source on the surface of the core material comprises:
[0049] The carbon source is dispersed in an organic solvent to obtain a dispersion, and the dispersion is then coated on the surface of the core material by spray drying.
[0050] In the present application, by controlling the concentration of the dispersion and the drying temperature of the spray drying, the coating state can be regulated, thereby controlling the specific surface area of the positive electrode material. The dispersion can be a suspension.
[0051] In some embodiments, the carbon source includes one or more of carbon nanotubes, graphene, carbon nanofibers, polydimethylsiloxane, polycarbonate, polyolefin, and polyacrylonitrile.
[0052] In some embodiments, the mass concentration of the carbon source in the dispersion is 10%-20%, for example, 10%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc.
[0053] In some embodiments, the drying temperature of spray drying is 60°C-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, etc.
[0054] In some embodiments, the organic solvent includes one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), toluene and carbon tetrachloride.
[0055] In some embodiments, the method for preparing the lithium phosphate positive electrode material comprises the following steps:
[0056] S11, providing a manganese source, an iron source, a phosphorus source and a lithium source or providing an iron source, a phosphorus source and a lithium source, mixing them, and grinding them with water to obtain a mixed solution;
[0057] S12, performing a second solid phase sintering on the mixed solution to obtain a lithium phosphate positive electrode material.
[0058] In the present application, the particle size of the positive electrode material can be adjusted by controlling the grinding time and the temperature of the second solid phase sintering.
[0059] In some embodiments, the grinding time is 2 h to 6 h, for example, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, etc.
[0060] In some embodiments, the temperature of the second solid-phase sintering is 300°C-1200°C, for example, it can be 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc., and the time of the second solid-phase sintering is 6h-12h, for example, it can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.
[0061] In some embodiments, the manganese source includes one or more of manganese tetraoxide, manganese trioxide, manganese sulfate, manganese carbonate, manganese oxalate, and manganese hydroxide.
[0062] In some embodiments, the iron source includes one or more of ferroferric oxide, ferric oxide, ferric hydroxide, ferrous sulfate, ferric sulfate, and ferric oxalate.
[0063] In some embodiments, the phosphorus source includes one or more of phosphoric acid, phosphate esters, lithium dihydrogen phosphate, iron phosphate, lithium phosphate, ammonium phosphate, and sodium phosphate.
[0064] In some embodiments, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium phosphate, lithium oxalate, lithium dihydrogen phosphate, and lithium sulfate.
[0065] In a third aspect, an embodiment of the present application further provides a positive electrode slurry, comprising the above-mentioned positive electrode material.
[0066] In some embodiments, the positive electrode slurry further includes a conductive agent, a binder, and a dispersant.
[0067] In some embodiments, in the positive electrode slurry, the mass percentage ratio of the positive electrode material, the conductive agent, the binder and the dispersant is (93.5%-98%): (0.1%-3%): (0.1%-3%): (0.1%-0.5%), for example, it can be 93.5%: 3%: 3%: 0.5%, 94.5%: 2%: 3%: 0.5%, 94.5%: 3%: 2%: 0.5%, 94.5%: 2.2%: 3% : 0.3%, 95.5%: 2%: 2%: 0.5%, 95.5%: 2.3%: 2%: 0.2%, 96.5%: 2%: 1%: 0.5%, 96.5%: 1%: 2%: 0.5%, 96.5%: 2.4%: 1%: 0.1%, 96.5%: 2%: 1.1%: 0.4%, 97.5%: 1%: 1%: 0.5%, 97.5%: 1.2%: 1.2%: 0.1%, etc.
[0068] In the present application, the preparation method of the positive electrode slurry can be prepared by directly dissolving the positive electrode material, the conductive agent, the binder and the dispersant in a solvent.
[0069] In a fourth aspect, an embodiment of the present application further provides a positive electrode plate, comprising a current collector and an active material layer disposed on the current collector, wherein the active material layer comprises the above-mentioned positive electrode material, and the contact angle θ of the surface of the active material layer to water is ≥55°.
[0070] In some embodiments, the contact angle θ of the surface of the active material layer to water is ≥55°, for example, it can be 55°, 56°, 57°, 58°, 59°, 60°, 61°, 62°, 63°, 64°, 65°, 66°, 67°, 68°, 69°, 70°, etc.
[0071] In the present application, the positive electrode sheet can be prepared by directly coating the positive electrode slurry on the current collector and drying it.
[0072] In a fifth aspect, an embodiment of the present application also provides a lithium battery, comprising the above-mentioned positive electrode plate.
[0073] Example 1
[0074] A positive electrode material and a preparation method thereof, comprising the following steps:
[0075] (1) adding manganese tetraoxide, iron phosphate, phosphoric acid, and lithium carbonate into a grinding jar at a molar ratio of 1:3:8:3, and adding water for physical grinding. After grinding for 2 hours, the mixture is solid-phase sintered at 300° C. for 8 hours to obtain a primary precursor;
[0076] (2) dispersing nitrified graphene (NGO) in NMP (the mass concentration of nitrified graphene is 10%), and uniformly coating the primary precursor by spray drying at a spray drying temperature of 60° C. to obtain a secondary precursor;
[0077] (3) The secondary precursor was solid-phase sintered at 800° C. in a N 2 atmosphere for 6 h to obtain a positive electrode material (the thickness of the carbon coating layer was 0.1 μm, and the mass content of the carbon coating layer in the positive electrode material was 1.8%).
[0078] A positive electrode slurry and a preparation method thereof, comprising the following steps:
[0079] The obtained positive electrode material was mixed with conductive carbon black (SP), polyvinylidene fluoride (PVDF), and polyisobutylene diimide (PI) in a mass ratio of 97.2%:0.9%:1.7%:0.2% in an N-methylpyrrolidone (NMP) solvent and stirred evenly to obtain a positive electrode slurry.
[0080] A positive electrode sheet and a preparation method thereof, comprising the following steps:
[0081] The obtained positive electrode slurry was evenly coated on a 12 μm thick aluminum foil and dried to obtain a positive electrode sheet.
[0082] Example 2
[0083] This embodiment is substantially the same as embodiment 1, except that the grinding time in this embodiment is 4 hours.
[0084] Example 3
[0085] This embodiment is substantially the same as embodiment 1, except that the grinding time in this embodiment is 6 hours.
[0086] Example 4
[0087] This embodiment is basically the same as embodiment 1, except that the sintering temperature in step (1) of this embodiment is 800°C.
[0088] Example 5
[0089] This embodiment is basically the same as embodiment 2, except that the sintering temperature in step (1) of this embodiment is 800°C.
[0090] Example 6
[0091] This embodiment is basically the same as embodiment 3, except that the sintering temperature in step (1) of this embodiment is 800°C.
[0092] Example 7
[0093] This embodiment is basically the same as embodiment 1, except that the sintering temperature in step (1) of this embodiment is 1200°C.
[0094] Example 8
[0095] This embodiment is basically the same as embodiment 2, except that the sintering temperature in step (1) of this embodiment is 1200°C.
[0096] Example 9
[0097] This embodiment is basically the same as embodiment 3, except that the sintering temperature in step (1) of this embodiment is 1200°C.
[0098] Example 10
[0099] This embodiment is substantially the same as Embodiment 1, except that the mass concentration of nitrated graphene in this embodiment is 15%.
[0100] Embodiment 11
[0101] This embodiment is substantially the same as Embodiment 1, except that the mass concentration of nitrated graphene in this embodiment is 20%.
[0102] Example 12
[0103] This embodiment is substantially the same as embodiment 1, except that the spray drying temperature in this embodiment is 70°C.
[0104] Example 13
[0105] This embodiment is substantially the same as embodiment 1, except that the spray drying temperature in this embodiment is 80°C.
[0106] Embodiment 14
[0107] This embodiment is substantially the same as embodiment 11, except that the spray drying temperature in this embodiment is 80°C.
[0108] Embodiment 15
[0109] This embodiment is substantially the same as the embodiment 1, except that in this embodiment, manganese tetraoxide, iron phosphate, phosphoric acid, and lithium carbonate are replaced with iron phosphate and lithium carbonate in a molar ratio of 1:1.
[0110] Example 16
[0111] This embodiment is basically the same as embodiment 1, except that the sintering temperature in step (1) of this embodiment is 1500°C.
[0112] Embodiment 17
[0113] This embodiment is substantially the same as embodiment 1, except that the grinding time in this embodiment is 10 h.
[0114] Embodiment 18
[0115] This embodiment is substantially the same as Embodiment 1, except that the mass concentration of nitrated graphene in this embodiment is 30%.
[0116] Embodiment 19
[0117] This embodiment is substantially the same as embodiment 1, except that the spray drying temperature in this embodiment is 100°C.
[0118] Comparative Example 1
[0119] This comparative example is basically the same as Example 1, except that the positive electrode material in this comparative example is not coated.
[0120] A lithium battery is made using the positive electrode sheets obtained in the embodiments and comparative examples, wherein the separator adopts a 7+2+2 mixed coating separator (the base film is a PE material with a thickness of 7 μm, and a coating with a thickness of 2 μm is respectively arranged on the upper and lower surfaces of the base film, and the coating material is a mixture of coated ceramic particles and PVDF glue particles); the electrolyte composition is 30 wt% of ethylene carbonate (EC), 5 wt% of propylene carbonate (PC), 25 wt% of ethyl methyl carbonate (EMC) and 40 wt% of dimethyl carbonate (DMC); the concentration of lithium salt (50% LiFSI+50% LiPF6) in the electrolyte is 1 mol / L; the negative electrode sheet is prepared by the following steps: graphite, conductive carbon black (Super P), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) are mixed with deionized water in a mass ratio of 8:1:0.5:0.5 to prepare an electrode slurry, which is then evenly coated on a 5 μm thick copper foil, and the negative electrode sheet is obtained after drying; the assembly method is lamination. The production process includes: electrode cutting, lamination, shelling, vacuum baking, liquid injection, standing, formation, and insulating film sticking.
[0121] Test example:
[0122] Cycle capacity retention rate test: The obtained lithium battery was fully charged and discharged at 25°C, and the cycle capacity retention rate was recorded. Full charge: At 25°C, charge at a constant current of 0.33C to the cut-off voltage (LFP3.65V, LMFP4.2V), then change to constant voltage charging with a cut-off current of 0.05C. Full discharge: At 25°C, discharge at 1C to 2.5V.
[0123] Contact angle test: After the positive electrode pieces are assembled into lithium batteries, the positive electrode pieces obtained by disassembling the lithium batteries are cleaned and dried. Water droplets are directly dropped on the surface of the positive electrode pieces. The droplet images are captured by an optical contact angle meter, and then the contact angle θ is automatically measured using software. The test results are shown in Table 1.
[0124] Table 1
[0125]
[0126] From Table 1 we can see that:
[0127] Compared with Examples 16-19, the contact angle of the positive electrode material of Example 1 is larger and the battery capacity retention rate is higher. It can be seen that by controlling the grinding time, sintering temperature, concentration of the carbon source dispersion, and spray drying temperature, the SSA / D50 of the positive electrode material can be regulated, thereby regulating the contact angle of the positive electrode material and further regulating the capacity retention rate of the battery.
[0128] Compared with Comparative Example 1, the contact angle of the positive electrode material of Examples 1-19 is larger and the battery capacity retention rate is higher. It can be seen that by coating a carbon coating layer on the surface of the lithium phosphate positive electrode material, the contact angle of the positive electrode material can be increased, thereby improving the capacity retention rate of the battery.
[0129] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A positive electrode material, characterized in that: The invention comprises a core body and a carbon coating layer, wherein the carbon coating layer is at least partially coated on the surface of the core body, the material of the core body comprises a lithium phosphate positive electrode material, and the carbon coating layer contains a hydrocarbon group 、 One or more groups of halogen atoms and nitro groups.
2. The positive electrode material according to claim 1, characterized in that: The lithium phosphate positive electrode material comprises at least one of lithium iron phosphate and lithium iron manganese phosphate; and / or The carbon coating layer is formed by carbonizing a carbon source, wherein the carbon source contains a hydrocarbon group 、 One or more groups of halogen atoms and nitro groups.
3. The positive electrode material according to claim 1, characterized in that: The positive electrode material satisfies: 14.5≤SSA / D50≤28.5, wherein SSA is the specific surface area of the positive electrode material, in m 2 / g, D50 is the particle size of the positive electrode material, in μm.
4. The positive electrode material according to claim 3, characterized in that: The SSA is 15m 2 / g-25m 2 / g; and / or The D50 is 0.5 μm-1.5 μm.
5. The positive electrode material according to claim 4, characterized in that: The thickness of the carbon coating layer is 0.1 μm-0.2 μm; and / or The mass content of the carbon coating layer in the positive electrode material is 1.5%-2.0%.
6. A method for preparing a positive electrode material, characterized in that: The following steps are involved: Providing a core material and a carbon source, and coating the carbon source on the surface of the core material to obtain a positive electrode material precursor, wherein the core material includes a lithium phosphate positive electrode material, and the carbon source includes one or more groups selected from hydrocarbon groups, halogen atoms, and nitro groups; The positive electrode material precursor is subjected to a first solid phase sintering to obtain a positive electrode material.
7. The method for preparing the positive electrode material according to claim 6, characterized in that: The step of coating the carbon source on the surface of the core material comprises: The carbon source is dispersed in an organic solvent to obtain a dispersion, and the dispersion is then coated on the surface of the core material by spray drying.
8. The method for preparing the positive electrode material according to claim 7, characterized in that: The carbon source contains hydrocarbon groups 、 One or more of halogen atoms, nitro groups; and / or The mass concentration of the carbon source in the dispersion is 10%-20%; and / or The drying temperature of the spray drying is 60°C-80°C.
9. The method for preparing the positive electrode material according to claim 6, characterized in that: The preparation method of the lithium phosphate positive electrode material comprises the following steps: Providing a manganese source, an iron source, a phosphorus source and a lithium source or providing an iron source, a phosphorus source and a lithium source, mixing them, and grinding them with water to obtain a mixed solution; The mixed solution is subjected to a second solid phase sintering to obtain a lithium phosphate positive electrode material.
10. The method for preparing the positive electrode material according to claim 9, characterized in that: The grinding time is 2h-6h; and / or The temperature of the second solid-phase sintering is 300° C.-1200° C., and the time of the second solid-phase sintering is 6 h-12 h.
11. The method for preparing the positive electrode material according to claim 6, characterized in that: The first solid phase sintering is performed under an inert gas atmosphere; and / or The temperature of the first solid-phase sintering is 300° C.-1200° C., and the time of the first solid-phase sintering is 6 h-12 h.
12. A positive electrode plate, characterized in that: It comprises a current collector and an active material layer arranged on the current collector, wherein the active material layer comprises the positive electrode material as described in any one of claims 1 to 5 or the positive electrode material prepared by the preparation method of the positive electrode material as described in any one of claims 6 to 11, and the contact angle θ of the surface of the active material layer to water is ≥55°.
13. A lithium battery, characterized in that: Comprising the positive electrode sheet as described in claim 12.
Citation Information
Patent Citations
Preparation method of lithium ion battery positive electrode material and lithium ion battery positive electrode material obtained through being prepared by method
CN107275594A
Process for protecting electrode materials against moisture
CN107851799A
Graphene lithium ion battery cathode material
CN111180680A
Modified lithium-containing phosphate positive electrode material as well as preparation method and application thereof
CN113594449A
Cathode material with low water content, preparation method thereof and lithium ion battery
CN114899371A
Cited By
Lithium iron phosphate positive electrode material, preparation method and pole piece
CN121076125A
Lithium iron phosphate positive electrode material, preparation method and electrode plate
CN121076125B
Positive electrode material and preparation method therefor, positive electrode sheet, and lithium battery
WO2026113231A1